Implementasi Pendekatan Holistik dalam Pembelajaran Bahasa Arab di MA Raudlatus Syabab Sukowono Jember - Nuzulus Sakinah; Ainur Rofiq Sofa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study analyzes the implementation of a holistic approach in Arabic language learning at MA Raudlatus Syabab Sukowono, Jember. The holistic approach emphasizes the integration of cognitive, affective, and psychomotor aspects to enhance students' overall Arabic language proficiency. This research employs a qualitative descriptive method with data collection techniques including observations, interviews, and documentation. The research subjects consist of Arabic language teachers, students, and educational staff involved in the learning process. Data analysis is conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that the holistic approach is implemented through project-based learning, group discussions, and the use of audiovisual media. Key supporting factors include the active role of teachers in guiding and motivating students, a conducive learning environment, and the availability of diverse learning media. However, challenges identified include limited instructional time and variations in student comprehension of the material taught. Despite these challenges, the holistic approach has proven effective in improving students' Arabic language proficiency when supported by appropriate teaching strategies that align with students' needs. This study recommends enhancing the role of teachers in the learning process, optimizing the use of learning resources, and developing adaptive strategies to maximize the effectiveness of Arabic language learning in the future.